Use of Wine and Dairy Yeasts as Single Starter Cultures for Flavor Compound Modification in Fish Sauce Fermentation - Gao, Pei; Xia, Wenshui; Li, Xinzhi; Liu, Shaoquan (Frontiers in Microbiology, 2019)
Effects of wine and dairy yeast fermentation on chemical constituents of tilapia fish head hydrolysate supplemented with glucose in an unsalted and acidic environment were investigated. Three wine yeasts (Torulaspora delbrueckii Biodiva, Saccharomyces cerevisiae Lalvin EC-1118 and Pichia kluyveri Frootzen) and one dairy yeast (Kluyveromyces marxianus NCYC1425) were employed as single starter cultures, respectively, and were compared with one soy sauce yeast (Candida versatilis NCYC1433). Each yeast showed different growth kinetics and fermentation performance. Compared with C. versatilis NCYC1433, other yeasts presented a significant higher rate of glucose consumption (P < 0.05). Besides, K. marxianus NCYC1425 and P. kluyveri Frootzen produced more citric acid and succinic acid, respectively, while S. cerevisiae Lalvin EC-1118 exhibited higher pyruvic acid production. Significant lower levels of total free amino acids were observed in samples inoculated with wine yeasts relative to other yeasts (P < 0.05). Non-soy sauce yeasts produced increased various levels of esters and alcohols without traditional fish sauce unpleasant odorants, especially K. marxianus NCYC1425 and P. kluyveri Frootzen. The results confirmed that non-soy sauce yeasts are suitable for fish sauce flavor modification and to develop a fast fermentation process for saltless fish sauce from fish head, which could increase the acceptability of fish sauce and improve the utilization of fish by-products.